Soil physics and rice (Los Banos, Philippines, 1985)
The book presents the physical aspects of soil management for rice-based cropping systems, the physical problems of wetland soil and water management, the physical aspects of wetland soil management from soil taxonomy. the evaluation of the physical environment for rice cultivation, the physical properties of mineral soils and of peat soils. The book also discusses problems of underdrainage of lowland rice fields, mineral composition of the clay fraction effecting soil behavior and management, influence of salinity and alkalinity on properties and management of ricelands. Finally, the book presents the soil-water management in lowland, the physical aspects of the root and seed environment in lowland soils, the water use and water use efficiency under different management system for upland crops
Keywords: Soil physics